CONSTRUCTION OF SPECIAL PHYSICAL FITNESS CHARACTERISTICS AND SCIENTIFIC TRAINING PLANS FOR MARTIAL ARTS SHORT-SOLDIER ATHLETES - WANG FENG, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Martial arts short-soldier sports is a competitive sport characterized by rapid offensive and defensive conversion and high-intensity confrontation, which puts forward high requirements for the special physical fitness level of athletes.With the continuous improvement of competition rules and the continuous improvement of competitive level, it is difficult for the traditional physical training model to fully meet the needs of the special development of martial arts short soldiers.On the basis of analyzing the characteristics of the martial arts short-soldier sports project, this paper systematically combs the core needs of the project for the special physical fitness of athletes, focusing on the special characteristics of physical fitness elements such as strength, speed, endurance, sensitivity and coordination, and combines modern sports training theory to construct a scientific physical training program that conforms to the laws of martial arts short-soldier sports.The research believes that clarifying special physical fitness characteristics and implementing scientific training are an important way to improve the competitive level of martial arts short-soldier athletes and extend their sports life.